Congenital or perinatal macules distributed according the Blaschko’s lines. - Schepis, C. (European Journal of Pediatric Dermatology, 2018)
We will discuss the differential diagnosis of the disorders with this pattern of distribution, namely 1- Incontinentia Pigmenti (IP), 2-Hypomelanosis of lto (Hl), 3- Epidermal Nevus (EN) and 4- Linear and Whorled Nevoid Hypermelanosis (LWNH), and we will underline their main characteristics.